Effect of three biowastes on the productivity potential of a sodic soil (2016)
Three biowastes were applied to a Typic Haplustepts sodic soil in order to generate a Soil Productivity Potential (SPP) indicator derived from the biological, physical and chemical properties. The biowastes included swine manure (SM), vinasse (VS) and composted biosolids (CB) incorporated on experimental plots and left undisturbed. The assessment of the soil properties was done prior to and twice during the experiment. The biowastes produced, in general, an increase in the SPP, being higher that of swine manure at the lowest dose in the short term, and composted biosolids at the highest dose in the long term; the vinasse did not significantly increase the SPP at any dose. In the control plots, in contrast, the SPP decreased steadily during the experiment period. The application of the three biowastes reduced the exchangeable sodium percentage, as well as the electric conductivity, particularly with the swine manure and composted biosolids at the low and high doses, respectively. The total porosity did not change significantly, whereas the CO2 production increased between all of the treatments and control. The SPP indicated that the biowaste addition improved the quality status of a sodic soil, particularly at the chemical level; hence, this practice could prevent the loss of productivity in the short and long term.